Rapid identification of cervus antlers by species-specific PCR assay. Issue 9 (2nd May 2020) - Yang, Yaya; Zheng, Yang; Lu, Beibei; Jiao, Zhaoqun; Chen, Liqun; Gblinwon, Roselyn Tehzee; Jia, Xiaobin; Shen, Yuping; Yang, Huan
Abstract: A rapid PCR technology was developed to differentiate Cervus antlers species and adulteration based on the difference in mitochondrial genome. Three specifically designed primer sets were confirmed to have high inter-species specificity and good intra-species stability. Limits of detection were estimated to be 1 ng of genomes for reindeer and 10 ng for the other species. Especially, when the mixture of Cervus antlers and reindeer or sambar was assayed, these primer sets still exhibited strong capability of differentiation but not the conventional COI barcoding. By using the newly developed approach, five batches out of fourteen commercial Cervus antler products were identified to be fake products made from reindeer antlers. It has shown its good potential to be extensively applied in the identification of counterfeits or adulterates of Cornu Chinese medicines for their pulverized and processed form, and even the traditional Chinese patent medicines composed of these species. Graphical Abstract: